Naturally cultured high resistant starch rice improved postprandial glucose levels in patients with type 2 diabetes: A randomized, double-blinded, controlled trial - Tan, Ling-li; Duan, Wei-qian; Chen, Meng-xue; Mei, Ying; Qi, Xiao-ya; Zhang, Yong (Frontiers in Nutrition, 2022)
Objective: To assess the effect of a novel naturally cultured rice with high resistant starch (RS) on postprandial glycemia in patients with type 2 diabetes compared to ordinary rice. Design: This study is a randomized, double-blinded controlled trial. Methods: Patients with type 2 diabetes were recruited, and postprandial glucose levels were measured at 5-time points after the ingestion of one of two types of cooked rice in random order. Paired t-tests were used to compare postprandial blood glucose changes and increment areas under the blood glucose curve between high-RS rice and ordinary rice. Results: The increments of the postprandial blood glucose levels for high-RS rice were significantly lower than that for ordinary rice, i.e., 2.80 ± 1.38 mmol/L vs 3.04 ± 1.50 mmol/L (P = 0.043) and 3.94 ± 2.25 mmol/L vs 4.25 ± 2.29 mmol/L (P = 0.036) at 30 minutes and 60 minutes，respectively. The incremental areas under the blood glucose curve for high-RS rice were also significantly lower than that for ordinary rice, i.e., 42.04 ± 20.65 [mmol/(L·min)] vs 45.53 ± 22.45 [mmol/(L·min)] (P = 0.043), 143.54 ± 69.63 [mmol/(L·min)] vs 155.15 ± 73.53 [mmol/(L·min)] (P = 0.026), and 354.61 ± 191.96 [mmol/(L·min)] vs 379.78 ± 195.30 [mmol/(L·min)] (P = 0.042) at 30, 60 and 120 minutes, respectively. Repeated-measures ANOVA showed that postprandial glucose levels were not affected by the test order. Conclusion: The novel high-RS rice as a staple food when substituting for widely consumed ordinary rice may provide potential health benefits by lowering blood glucose in patients with type 2 diabetes. Keywords: resistant starch (RS), rice, diabetes, postprandial glucose level, randomized controlled trial (RCT)